2013
DOI: 10.1039/c2tc00304j
|View full text |Cite
|
Sign up to set email alerts
|

Capsule-embedded reduced graphene oxide: synthesis, mechanism and electrical properties

Abstract: We report the synthesis of capsule-embedded reduced graphene oxide (rGO) by photocatalytic reduction in the presence of peanut shaped a-Fe 2 O 3 particles under visible light. This process is able to produce highly stabilized water dispersible rGO without the help of a stabilizer, which is suitable to make thin films on a glass substrate by the drop casting method. In addition, the evolution of the morphology with different visible light exposure times ranging from 5 to 120 minutes reveals that the catalyst le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…46 For UV-vis spectrum of CuO-rGO nanocomposites, it is observed that the peak in GO spectrum at 230 nm is shied to 256 nm due to the reduction GO sheet and the characteristic peak of CuO nanoparticles appeared at 375 nm. 46,47 Also, the characteristics peak of AgNPs appeared at 400 nm in the spectrum of Ag-rGO and Ag/CuO-rGO nanocomposites which conrms the presence of AgNPs on GO surface. 48 The structures and phase composition of all prepared samples were examined by using XRD measurements and the corresponding pattern is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…46 For UV-vis spectrum of CuO-rGO nanocomposites, it is observed that the peak in GO spectrum at 230 nm is shied to 256 nm due to the reduction GO sheet and the characteristic peak of CuO nanoparticles appeared at 375 nm. 46,47 Also, the characteristics peak of AgNPs appeared at 400 nm in the spectrum of Ag-rGO and Ag/CuO-rGO nanocomposites which conrms the presence of AgNPs on GO surface. 48 The structures and phase composition of all prepared samples were examined by using XRD measurements and the corresponding pattern is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optical band gap (E g ) of RGO and SRGO were estimated using the Tauc-David Mott equation (eqn (1)). [21][22][23][24][25]…”
Section: Morphological Structural and Optical Characterizationmentioning
confidence: 99%
“…To identify the GO content, UV-Vis spectroscopic studies were performed, Figure 3 . It is inferred that the presence of GO contents is identified through the optical absorption of GO dominated by the π–π stacking at about the more intense peak of 230 nm [ 33 , 34 ]. The π–π stacking peak on film samples with GO contents was recorded with a blue shift when compared with GO at 212, 213, 216, and 220 nm for F2-16, F2-8, F1-8, and F1-16, respectively.…”
Section: Resultsmentioning
confidence: 99%